Experience of Filipinos with Spinal Cord Injury in the Use of Assistive Technology: An Occupational Justice Perspective - Daryl Patrick G. Yao; Kaoru Inoue; Michael P. Sy; Peter Bontje; Natsuka Suyama; Chiyomi Yatsu; Dante A. Perez; Yuko Ito (Occupational Therapy International)
Assistive technology (AT) is often required to facilitate the performance of occupations and promote inclusion and reduction of dependency among persons with spinal cord injury (SCI). However, only 5-15% of individuals in developing countries have access to AT. This study is aimed at exploring the experience of Filipinos with SCI as they use AT and understand these from an occupational justice (OJ) perspective. This study utilised a hermeneutic phenomenological approach to explore the participants’ experiences with AT usage. Ten participants were recruited from a hospital and communities within Metro Manila, Philippines, and interviewed last January 2020. Hermeneutic analysis was done to interpret the shared meaning embedded within their experiences and was informed by an occupational justice perspective. Exploring the experience of the participants in using AT yielded four themes, namely, (1) engaging in occupations despite limited opportunities, (2) going to various locations amidst an inaccessible environment, (3) striving towards inclusion in spite of attitudinal barriers, and (4) securing needs in light of unfavourable life conditions. Filipinos with SCI deal with numerous structural and contextual factors in daily life. There has been partial enablement of OJ as they incorporate AT in their daily lives as occupational rights are far from being recognised and respected. In infusing an OJ perspective to understanding AT use, OT practitioners are bound to identify problems and courses of action that go beyond traditional service delivery.